Metarhizium microsclerotia and hydrogel versus hydromulch: testing fungal formulations against Asian longhorned beetles. Issue 8 (3rd August 2017) - Gardescu, Sana; Hajek, Ann E.; Goble, Tarryn A.; Jackson, Mark A.
ABSTRACT: The efficacy of microsclerotia of Metarhizium brunneum (Petch) (Hypocreales: Clavicipitaceae) strain F52 (ARSEF 7711) was tested using samples which had been exposed on forest trees, allowing time for conidia to be produced. An aqueous slurry of microsclerotial granules (61.3% of dry mass), a straw mulch hydroseeding product (29.4%), xanthan gum as a tackifier (5.4%), and water-absorbing hydrogel (3.9%), was sprayed on small wood-veneer samples attached to tree trunks within the Ohio USDA quarantine zone for eradication of Asian longhorned beetles, Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae). Samples were collected biweekly June to August, and adult female beetles in a quarantine laboratory were exposed for 2 days to individual samples after each collection. Median survival time (ST50 ) after exposure to samples which had been outdoors four weeks was 9.5 days (95% CI 8.5–10.5); the beetles died faster than with samples from 2 or 6–10 weeks, but slower than using positive control microsclerotial samples (ST50 6.5 days). Conidial density of field-collected samples peaked at 4 weeks, while the sprayed material gradually weathered to 33% of initial dry mass by 10 weeks. A separate field experiment in New York State compared three formulations: the hydrogel–hydromulch mixture, straw hydromulch without hydrogel, or hydrogel alone. Results were highly weather-dependent, but median beetle survival in the August bioassays was between 8.5–9.5 days for all three formulations. Overall, the hydrogel addition did not significantly improve efficacy, either during dry or rainy periods, and hydrogel alone (without hydromulch) appeared to be an additional viable option.